Kebijakan Moneter Di Tengah Pandemi Covid-19 - Rifqi Al Faris, Muhammad; Dwi Rahamawati, Putri; Natalya, Fajratun (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Abstract: World economic growth has slowed down. One of the reasons for the slowdown in economic growth is the outbreak of the corona virus. This economic downturn is likely to result in sluggishness in the business investment sector, so that the banking sector will also experience the impact. So that it is necessary to determine a monetary policy by the government that is able to provide protection and can survive amidst the onslaught of the world economic slowdown due to the corona virus outbreak. This study aims to examine monetary policies issued by the world government and also the Indonesian government to prevent a slowdown in economic growth during the Covid-19 period. Using a qualitative approach by conducting a literature analysis of books, articles, and news. This research provides the results of many countries in the world that have cut interest rates and repurchased bonds that have been issued. Bank Indonesia also briefly lowered the interest rate to 4.5% and relaxed the reserve requirement by up to 50 bps. Abstrak: Pertumbuhan ekonomi dunia mengalami perlambatan. Salah satu penyebab perlambatan pertumbuhan perekonomian adalah wabah penyakit corona virus. Penurunan perekonomian ini berkemungkinan akan mengakibatkan kelesuan pada sektor investasi bisnis, sehingga sektor perbankan juga akan mengalami dampaknya. Sehingga diperlukan penentuan kebijakan moneter oleh pemerintah yang mampu memberikan pelindungan serta dapat bertahan ditengah gempurn perlambatan perekonomian dunia akibat mewabahnya virus corona. Penelitian ini bertujuan untuk menelaah kebijakan moneter yang dikeluarkan oleh pemerintah dunia dan juga pemerintah Indonesia untuk mncegah perlambatan pertumbuhan perekonomian pada masa Covid-19. Menggunakan pendekatan kualitatif dengan melakukan analisis literatur dari buku, artikel, maupun berita. Penelitian ini memberikan hasil banyak negara di dunia yang melakukan pemangkasan tingkat suku bunga dan melakukan pembelian kembali obligasi yang telah dikeluarkan. Bank Indonesia juga sempat menurunkan tingkat suku bunga menjadi 4,5% dan melonggarkan GWM hingga 50 bps.